Oral delivery of Brucella spp. recombinant protein U-Omp16 abrogates the IgE-mediated milk allergy - Smaldini, Paola Lorena (2014)
Food allergies are increasingly common disorders and no therapeutic strategies are yet approved. The unlipidated Omp16 (U-Omp16) is the outer membrane protein of 16 kDa from B. abortus and possesses a mucosal adjuvant property. In this study, we aimed to examine the U-Omp16 capacity to abrogate an allergen-specific Th2 immune response when it is administered as an oral adjuvant in a mouse model of food allergy. Balb/c mice were sensitized with cholera toxin and cow's milk proteins (CMP) by gavage and simultaneously treated with U-Omp16 and CMP. Oral challenge with CMP was performed to evaluate the allergic status of mice. Symptoms, local (small bowel cytokine and transcription factor gene expression) and systemic (specific isotypes and spleen cell-secreted cytokines) parameters, and skin tests were done to evaluate the immune response. We found that the oral administration of U-Omp16 with CMP during sensitization dampened the allergic symptoms, with negativization of immediate skin test and increased skin DTH response. Serum specific IgE and IL-5 were inhibited and a Th1 response was promoted (specific IgG2a antibodies and CMP-induced IFN-γ secretion). We found at the mucosal site an inhibition of the gene expression corresponding to IL-13 and Gata-3, with an induction of IFN-γ and T-bet. These results indicated that the oral administration of U-Omp16 significantly controlled the allergic response in sensitized mice with a shift of the balance of Th1- and Th2-T cells toward Th1 predominance. These findings suggest that U-Omp16 may be useful as a Th1-directing adjuvant in an oral vaccine.